DRAMATIC DANCE WORK WITH THE TITLE " PUNARBHAVA " AS AN EXPRESSION OF THE MEANING OF THE CAKRA PALAH BATIK MOTIF - Putra Atmaja, Aditya; Dwi Sasandjati, Jajuk (Solah, 2025)
The dramatic dance work “Punarbhava” is an artistic expression born from deep contemplation of the meaning behind the Cakra Palah batik motif, a cultural symbol of Blitar Regency that holds profound philosophical values about the cycle of human life. The primary inspiration for this work stems from the philosophy of Cakra Manggilingan, which conveys the idea that life continuously turns — from glory to downfall, and then rises again with newfound wisdom. In this piece, the choreographer seeks to express the spiritual message that true fulfillment in life is not defined by luxury or power, but by the awareness of one’s limitations as a creation of God. Using a dramatic dance form with a double-climax structure, Punarbhava presents intense emotional dynamics in each scene. Rather than delivering a linear narrative, it emphasizes moods and inner conflicts through explorations of movement, expression, makeup, costume, and stage patterns that blend into one cohesive whole. The creative process incorporates Jacqueline Smith’s Construction Method I — starting from exploration, improvisation, and evaluation, to refinement — to convey the concept fully and aesthetically. As an expression of love for local cultural heritage, Punarbhava serves not only as a personal form of artistic expression but also as a contribution to introducing the cultural values of Blitar to a broader audience. Through this work, the Cakra Palah batik motif is no longer confined to visual patterns on fabric, but transforms into living, touching, and inspiring body movements. This dance is hoped to open a dialogue between traditional arts, spirituality, and local identity that remains relevant in today’s evolving era. Keywords: dance work, punarbhava, batik cakra palah.